Meningkatkan Minat Mahasiswa Menjadi Nasabah Bank Mini Syariah UNIRA Malang - Sukma Nur Avivah; Hilda Sanjayawati (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This service activity aims to encourage students to become customers of the Unira Malang Sharia Mini Bank. This service use a descriptive approach. To collect data using observation. The results of the service show that there are several steps that can be taken to encourage students to become customers of sharia mini bank, namely : carrying out promotions, providing education regarding sharia mini banks to students, and excellent service. Development of BMS on campus to assist campus financial management, which includes planning and implementing mini bank functions to assist financial management and mini bank development plans for the sustainability of future mini bank programs.